Do not Stop: The Importance of Seamless Monitoring and Enforcement in an Indonesian Marine Protected Area. (2nd August 2011) - Mangubhai, Sangeeta; Saleh, Muhammad; Suprayitno,; Muljadi, Andreas; Purwanto,; Rhodes, Kevin L.; Tjandra, Katherina
Abstract : The harvesting of groupers (Serranidae) in Indonesia for the live reef food fish trade (LRFFT) has been ongoing since the late 1980s. Eight sites in Komodo National Park that included two fish spawning aggregation (FSA) sites were monitored for groupers and humphead wrasse, Cheilinus undulatus, from 1998 to 2003 and from 2005 to 2008 to examine temporal changes in abundance and assess the effectiveness of conservation and management efforts. Monitoring identified FSA sites for squaretail coralgrouper, Plectropomus areolatus, and brown-marbled grouper, Epinephelus fuscoguttatus . Both species formed aggregations before and during full moon from September to December, prior to lapses in monitoring (2003–2005) and in enforcement (2004-2005). Following these lapses, data reveal substantial declines in P. areolatus abundance and the apparent extirpation of one aggregation at one site. Other non-aggregating species targeted by the LRFFT showed similar declines at three of eight monitored sites. This paper highlights the impact of FSA fishing and the need for a seamless monitoring and enforcement protocol in areas where aggregation fishing pressure is high. Within Komodo National Park, local fishers, particularly those operating on behalf of the LRFFT, pose a serious threat to population persistence of species targeted by this trade.